Divergent selection predating the Last Glacial Maximum mainly acted on macro‐phenotypes in Norway spruce. (20th December 2022) - Tiret, Mathieu; Olsson, Lars; Grahn, Thomas; Karlsson, Bo; Milesi, Pascal; Lascoux, Martin; Lundqvist, Sven‐Olof; García‐Gil, Maria Rosario
Abstract: The current distribution and population structure of many species were, to a large extent, shaped by cycles of isolation in glacial refugia and subsequent population expansions. Isolation in and postglacial expansion through heterogeneous environments led to either neutral or adaptive divergence. Norway spruce is no exception, and its current distribution is the consequence of a constant interplay between evolutionary and demographic processes. We investigated population differentiation and adaptation of Norway spruce for juvenile growth, diameter of the stem, wood density, and tracheid traits at breast height. Data from 4461 phenotyped and genotyped Norway spruce from 396 half‐sib families in two progeny tests were used to test for divergent selection in the framework of Q ST vs. F ST . We show that the macroscopic resultant trait (stem diameter), unlike its microscopic components (tracheid dimensions) and juvenile growth, was under divergent selection that predated the Last Glacial Maximum. Altogether, the current variation in these phenotypic traits in Norway spruce is better explained by local adaptation to ancestral environments than to current ones, where populations were partly preadapted, mainly through growth‐related traits.